Pengaruh Modal Kerja dan Jam Kerja Terhadap Pendapatan Pedagang Kaki Lima Nasi Boran di Lamongan - Fatmah Nitami; Erwin Dyah Astawinetu (EBISMAN eBisnis Manajemen, 2024)
This study has an objective in knowing whether or not there is an influence between working capital and working hours related to the income of boran rice street vendors in Lamongan. The study method is through a quantitative approach with data collection through a Likert scale questionnaire. The population of Boran rice sellers is 87 people so that by using the Slovin formula, 47 respondent samples are obtained which will be randomly selected. The data will be tested with multiple linear regression analysis. This research shows that the influence of capital and working hours is positive and significant both simultaneously and partially with a percentage of 95.1% where this result is close to 100% so that the implication of this study is that traders, especially street vendors, must infuse capital and working hours, it is hoped that the growth in stock of goods can attract buyers' attention and contribute to an overall increase in income.